A Study of Mercury Pollution in Water, Sediment, and Lais (Kryptopterus) Fish in the Melawi Watershed - Triswanto, Bambang; Widodo, Muhammad Agus; Ardiningsih, Puji (Journal of Tropical Life Science, 2020)
Mercury (Hg) is a heavy metal that is very dangerous and toxic. Melawi River, a river with a length of 471 m, passes through four districts namely Menukung, Ella Hulu, Ella Hilir, and Nanga Pinoh which are the main water transportation routes in Melawi regency. This research was aimed to determine the concentration of mercury in water, sediments and Lais (Kryptopterus) fish of mercury bioconcentration factors, and the safety level of consumption the contaminated Lais (Kryptopterus) fish. The mercury measurement using Atomic Absorption Spectroscopy (AAS) showed that the average concentration of mercury found in the water was 1.80Ã—10-4 ppm, sediments 1.33Ã—10-2 ppm, and Lais fish 0.291 ppm. Meanwhile, the average bioconcentration factor (BCF) of mercury in Lais fish was 1.677 ppm. The maximum daily consumption of Lais fish that were safe for the community consumption at the Melawi watershed was 0,026 kg /day for adults and 0.006 kg/day for the children.